An investigation of tetrahydrocannabinol, cannabidiol and cannabinol content of cannabis confiscated by the South African Police Service's Forensic Laboratories from various regions of South Africa - Londt, Rolanda Sabrina (Division of Forensic Medicine and Toxicology, 2014)
Includes abstract. Includes bibliographical references.